Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.31234/osf.io/bhxwp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal Dynamics of Partisan Identity Fusion and Prosociality 
during the 2016 U.S. Presidential Election

Abstract: We investigated the dynamics of identity fusion and prosocial behavior within political groups in the four weeks preceding and following the 2016 U.S. Presidential Election. The primary questions were whether a negative event (losing) would lead to a more pronounced increase in identity fusion, and whether identity fusion would predict prosocial giving. We found that while fusion gradually increased in the run-up to the election, there was no significant increase after the event for supporters of either party.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In support of this possibility, a study by Segal, Jong, and Halberstadt () found that strongly fused individuals’ prosociality was linked to their greater perceptions of harm in an agentless event (i.e., an earthquake) to which fused individuals nevertheless ascribed an agent. Indeed, identity fusion has consistently been linked to heightened feelings of both progroup agency (Swann et al, ) and prosociality (e.g., Misch, Fergusson, & Dunham, ). Thus, from a dyadic morality perspective, fused individuals’ moral sensibility may be undergirded by heightened feelings of moral responsibility and blame in response to the perceived suffering of group members.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this possibility, a study by Segal, Jong, and Halberstadt () found that strongly fused individuals’ prosociality was linked to their greater perceptions of harm in an agentless event (i.e., an earthquake) to which fused individuals nevertheless ascribed an agent. Indeed, identity fusion has consistently been linked to heightened feelings of both progroup agency (Swann et al, ) and prosociality (e.g., Misch, Fergusson, & Dunham, ). Thus, from a dyadic morality perspective, fused individuals’ moral sensibility may be undergirded by heightened feelings of moral responsibility and blame in response to the perceived suffering of group members.…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies conducted since 2015 confirm that fusion motivates individuals to engage in several kinds of actions to protect or defend the entity with which they are fused, in addition to the traditional outcome measure of willingness to fight and die for the group. What they do seems to be determined by the kind of entity they are fused with as well as by some situational factors (e.g., Fredman et al, 2017; Misch, Ferguson, & Durnham, 2018; Newson, Buhrmester, & Whitehouse, 2016; Vázquez et al, 2017). For instance, people who strongly fuse with an outgroup that is victim of unjust treatment, like the Palestinians or the Kurds, are more willing to participate in extreme forms of protest on behalf of the group (Kunst et al, 2018); whereas people who fuse with an activity related to a brand are more willing to spread negative world‐of‐mouth, to boycott the brand, and to avoid repurchasing the brand after a market disruption or a brand transgression (Hawkins, 2019).…”
Section: Main Advances and Discoveries Since 2015 For Identity Fusionmentioning
confidence: 99%
“…The premise of our experimental design is to use the Dictator Game (DG) to compare how willing crowdworkers on MTurk are to cooperate with each other, with crowdworkers from a different platform, or with random strangers. We elected to use a DG because it reflects consequential real-world behavior (i.e., giving money), and while it is frequently conceptualized as a measure of generosity, in intergroup contexts it directly relates to social identification (Misch, Fergusson, & Dunham, 2018;Peysakhovich & Rand, 2017) and so can serve as a behavioral indicator of group alignment. To determine a realistic floor in giving, we also include an additional condition in which "donated" money is destroyed, that is, lost to all parties including the donating participant.…”
Section: The Present Studymentioning
confidence: 99%